Delirium-related factors and their prognostic value in patients undergoing craniotomy for brain metastasis - Yoo, Jihwan; Joo, Bio; Park, Juyeong; Park, Hun Ho; Park, Mina; Ahn, Sung Jun; Suh, Sang Hyun; Kim, Jae-Jin; Oh, Jooyoung (Frontiers in Neurology, 2022)
Background Delirium is characterized by acute brain dysfunction. Although delirium significantly affects the quality of life of patients with brain metastases, little is known about delirium in patients who undergo craniotomy for brain metastases. This study aimed to identify the factors influencing the occurrence of delirium following craniotomy for brain metastases and determine its impact on patient prognosis. Method A total of 153 patients who underwent craniotomy for brain metastases between March 2013 and December 2020 were evaluated for clinical and radiological factors related to the occurrence of delirium. Statistical analysis was conducted by dividing the patients into two groups based on the presence of delirium, and statistical significance was confirmed by adjusting the clinical characteristics of the patients with brain metastases using propensity score matching (PSM). The effect of delirium on patient survival was subsequently evaluated using Kaplan–Meier analysis. Results Of 153 patients, 14 (9.2%) had delirium. Age (P = 0.002), sex (P = 0.007), and presence of postoperative hematoma (P = 0.001) were significantly different between the delirium and non-delirium groups. When the matched patients (14 patients in each group) were compared using PSM, postoperative hematoma showed a statistically significant difference (P = 0.036) between the delirium and non-delirium groups. Kaplan–Meier survival analysis revealed that the delirium group had poorer prognosis (log-rank score of 0.0032) than the non-delirium group. Conclusion In addition to the previously identified factors, postoperative hematoma was identified as a strong predictor of postoperative delirium. Also, the negative impact of delirium on patient prognosis including low survival rate was confirmed.